Sibling Indices as Comparisons in Personal Identification Process through Short Tandem Repeats [STR] Loci CSF1PO, THOI, TPOX, vWA of Maduranese Ethnic in Surabaya - Ahmad Yudianto; Fery Setiawan; Simon Martin Manyanza Nzilibili (Journal of Tropical Biodiversity and Biotechnology, 2021)
Sibling indices can be used as a comparison through alleles Short Tandem Repeats [STR] loci. This is an observational study among Maduranese with 4 STR loci (CSF1PO, THOI, TPOX, vWA) obtained from their blood samples. The percentage of alleles shared: 82.5% [33 times] with 2 allele sharing, 12.5% [5 times] with 1 allele sharing, and 5 % [2 times] with 0 sharing alleles. Sibling indices (SI) calculation results: 65% of sibling indices pairs have SI greater than 100 and 15% of them were between 10-100 (strong and very strong). Sibling indices interpretation is supported; therefore, the claimed sibling indices relationships were indeed true among Maduranese ethnic group in Surabaya.